Gas-assisted evaporation and boiling in minichannels. (January 2018) - Fu, Ben-Ran; Chen, Ya-Chin; Ho, Ming-Xi; Pan, Chin
Highlights: Helium–ethanol flow in minichannels were studied in non-boiling and boiling regions. The heat transfer enhancement (HTE) and corresponding flow patterns were explored. The maximal HTE owing to an inert gas is located at the wall superheat of −10 °C. The HTE increases with an increase in the helium flow rate. The maximal HTE is 206% (or 129%) in the parallel (or single) minichannels. Abstract: This study experimentally explores the heat transfer characteristics of gas-assisted evaporation and boiling in single or two parallel minichannels under both non-boiling and boiling conditions. The liquid working fluid used is ethanol and the inert gas is helium. Compared to the pure ethanol flow in a minichannel under both non-boiling and boiling conditions, the heat transfer enhancement (HTE) caused by the adjunction of helium is examined. The maximal HTE owing to an inert gas is located at the wall superheat (Δ Tsat ) of −10 °C (i.e., non-boiling region) in the single minichannel in which the annular flow occurring in most parts of the channel; however, for the boiling region, the HTE is insignificant in the single minichannel, as the flow patterns observed for the studied cases are approximately the same. For the two parallel minichannels, the differences in the mean (effective) wall heat flux between the cases with and without helium become much more evident than those in a single minichannel. Under boiling conditions, primarily an annular flow, accompanied with bubble nucleation at the wall downstream, occurs for the studied cases when helium flow is present; however, extensive bubble nucleation occurs and bubbly flow prevails for the case without helium flow. Owing to the difference in flow pattern, the heat transfer performances for the cases with and without helium are significantly different in the parallel minichannels under this boiling condition. In addition, the HTE significantly increases with an increase in the helium flow rate at a given wall superheat. The maximal HTE, which also occurred at about Δ Tsat  = −10 °C, is 206% obtained under the conditions of the lowest ethanol flow rate and the highest helium flow rate in the parallel minichannels.